solve. 2(x)+5=9

Guide :

solve. 2(x)+5=9

Equations.

Research, Knowledge and Information :


Solve for x 2 +5 = 9 - Kansas State Mathematics Department


Solve for x. 2x¡3 = 5 3x+7 = 1 ¡2x+5 = 9 2 3 x ...
Read More At : www.math.ksu.edu...

Solve Equation with Steps Step-by-Step Math Problem Solver


3x + 3 = x + 13, 3x = x + 10, 2x = 10, and x = 5. are equivalent equations, because 5 is the only solution of each of them. ... Example 3 Solve 2x + 1 = x - 2.
Read More At : quickmath.com...

2x-5=9 - Get Easy Solution


Simple and best practice solution for 2x-5=9 equation. Check how easy it is, and learn it for the future. ... SOLVE: Solution for 2x-5=9 equation: 2x - 5 = 9
Read More At : www.geteasysolution.com...

Solve the Equation 2x-5=9 - Answer | Math Problem Solver - Cymath


Get the answer to Solve the Equation 2x-5=9 with the Cymath math problem solver - a free math equation solver and math solving app for calculus and ... [2x-5=9
Read More At : www.cymath.com...

How do you solve (1/2(x-6)+2x)/-5 = 9/10? | Socratic


... /-5=9/10 or 1/2(x-6)+2x=-5times9/10 or x/2-3+2x=-9/2 or (5x)/2=3-9/2 or (5x)/2=-3/2 or 5x=-3 or x=-3/5. ... How do you solve #int x^-4*sqrt(x^4+1)# ?
Read More At : socratic.org...

Home | MIT - Solve


Become part of Solve’s global community and enjoy these member benefits: Access to Solve events; A stake in Solve’s challenge agenda; Connections with other ...
Read More At : solve.mit.edu...

Solving One-Step Linear Equations (page 2 of 4) - Purplemath


Solving One-Step Linear Equations (page 2 of 4) Sections: One-step equations, Multi ... of the equation by whatever is multiplied on the x: Solve 2x = 5 ...
Read More At : www.purplemath.com...

-3< 5-2x< 9 - Inequalities Calculator - Symbolab


Free inequality calculator - solve linear, quadratic and absolute value inequalities step-by-step. ... (x+5)(x-5)\gt 0; 2x^2-x\gt 0 \left(x+3\right)^2\le 10x+6 \left ...
Read More At : www.symbolab.com...

How do you solve 2x-5/9 = (7x+8)/9? | Socratic


To do that multiply everything by 9; 18x-5=7x+8 2. ... How do you solve #2x-5/9 = (7x+8)/9#? ... How do you solve #root3(3x - 8) ...
Read More At : socratic.org...

Suggested Questions And Answer :


How do I solve y=-x-4

How do I solve y=-x-4 I need to be able to plot these points on a graph but i don't know how to solve the problem.   make an x & y axis. ( like a cross one line goes vertical an the other horizontal) put equal dimention for x & y line From center line moving
Read More: ...

how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero an
Read More: ...

How do you solve this problem? solve for d: n= m+3d/4

Problem: How do you solve this problem? solve for d: n= m+3d/4 I need help solving this and seeing how it was solved since I am having trouble figuring out what to do and how to solve it thanks. n = m + 3d/4 n - m = (m + 3d/4) - m n - m = 3d/4 4(n - m) = (3d/4)4 4(n - m) = 3d 4(n - m)/3 = 3
Read More: ...

Solve, using linear combination. 3x + y = 4 2x + y = 5

line 1: 3x+y=4    or y=4-3x line 2: 2x+y=5 line 1 -line2...(3x-2x)+(y-y)=4-5 or x=-1 y=4-3x=4+3=7
Read More: ...

how can i solve these equations?

how can i solve these equations? x + 3y – z = 2 x – 2y + 3z = 7 x + 2y – 5z = –21 We eliminate one of the unknowns (x, y or z, take your choice), leaving two unknowns. Then, we eliminate a second one, giving us an equation with only one of the unknowns. Solve for that and plug that value in
Read More: ...

Inequalities

9x+6=51 9x=51-6 9x=45 x=5
Read More: ...

how do you solve 3/x+5

how do you solve 3/x+5 I'm confused on how to solve this problem All you have is an expression. There is nothing to solve until you make it an equation. 3/x + 5 = -8 3/x + 5 = 14 3/x + 5 = 0 3/x + 5 = 38.67 3/x + 5 = -91 3/x + 5 = 43 Those can be solved, because they are complete. Each one will h
Read More: ...

x - z = -3, y + z = 9, -2x + 3y +5z = 33

Problem: x - z = -3, y + z = 9, -2x + 3y +5z = 33 1) x - z = -3 2) y + z = 9 3) -2x + 3y + 5z = 33 Add equation 2 to equation 1.      x     - z = -3 +(    y + z =  9) ------------------   x + y     = 6 4)
Read More: ...

how to solve by substitution

how to solve by substitution .3x+3y=1.2(100) "Substitution" implies there are TWO equations in two unknowns. You solve one of them for one of the unknowns in terms of the other, e.g., solve for y in terms of x. THEN, you substitute that value into the other equation where the y is, and yo
Read More: ...

2x+y=9 x-2z=-3 2y+3z=15

2x+y=9 x-2z=-3 2y+3z=15 Forgot how to do This. Problems Solving systems of this type requires eliminating all but one unknown so you can solve for that unknown. Then, plug that value into one of the equations to solve for another of the unknowns. Finally, plug both of those values into an equation
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.painphr.com || Terms of Use || Contact || Privacy Policy
Load time: 0.0836 seconds